An Analysis of Kindergarten’s Conversation Skills Through Comma 2.0 Application as an Audio-Visual-Based Learning Medium - Kinanti resmi Hayati; tranggono tranggono; Navisatul Izzah; fitriatus sholehah; Heru Prasetiyo Utomo; Radityo Anggoro (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
This study aims to evaluate English conversational skills in early childhood through the use of the Comma 2.0 application as a learning medium. The research method follows an experimental approach, applying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) in instructional design. In the analysis stage, we identified the needs and characteristics of early childhood learners in English language acquisition. We then designed the lessons by integrating the audio-visual-based Comma 2.0 application, adhering to instructional design principles that are engaging and suitable for early childhood development. The implementation was conducted with two groups: a control group using conventional learning methods and an experimental group using the Comma 2.0 application. Evaluation was performed before and after the intervention using English conversation skill tests. The results showed a significant improvement in the experimental group, validating the effectiveness of the Comma 2.0 application in enhancing English conversational skills in early childhood. These findings support the use of technology-based learning approaches in early childhood development, creating an interactive and engaging learning environment.